2021
DOI: 10.1039/d0nr07819k
|View full text |Cite
|
Sign up to set email alerts
|

Extended curly arrow rules to rationalise and predict structural effects on quantum interference in molecular junctions

Abstract: An extension to curly arrow rules for the prediction of quantum interference behaviour in conjugated molecular wires widens the scope of this simple graphical method to wires containing heteroatoms, cross-conjugation and/or non-alternant structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 80 publications
(218 reference statements)
0
32
1
Order By: Relevance
“…However, computational studies showed this was a steric rather than an electronic effect; enhanced conductance was seen in the transmission function if the methoxy substituent was constrained to an unfavourable position in which its lone pair could interact with the OPE π-system. 153 These 132,153 and other studies [34][35][36] have related the increased conductance associated with the addition of heteroatoms to meta-linked OAEs to the electron-withdrawing or -donating properties of the heteroatom(s). Charge transport simulations showed that the presence of donor or acceptor groups at certain positions shifted DQI antiresonances away from E F , meaning T (E) and hence conductance was higher in this region.…”
Section: Aromaticity and Heteroatom Effectsmentioning
confidence: 95%
See 4 more Smart Citations
“…However, computational studies showed this was a steric rather than an electronic effect; enhanced conductance was seen in the transmission function if the methoxy substituent was constrained to an unfavourable position in which its lone pair could interact with the OPE π-system. 153 These 132,153 and other studies [34][35][36] have related the increased conductance associated with the addition of heteroatoms to meta-linked OAEs to the electron-withdrawing or -donating properties of the heteroatom(s). Charge transport simulations showed that the presence of donor or acceptor groups at certain positions shifted DQI antiresonances away from E F , meaning T (E) and hence conductance was higher in this region.…”
Section: Aromaticity and Heteroatom Effectsmentioning
confidence: 95%
“…Certain structural features can cause antiresonances to be shifted away from E F and thereby reduce their impact on conductance. [34][35][36] Fig. 3 Cartoon illustrating the MCBJ method.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
See 3 more Smart Citations